The Requirements of the Smart Safety Management System and its Role in Achieving Production Excellence: Analytical study of the opinions of workers in two samples of cement plants in Sulaymaniyah Governorate / Kurdistan Region of Iraq - Rahim, Sarhang Mohammed; Hama Kareem, Jamal Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Although there has been a significant increase in the reliability of machinery and equipment over the years in the production processes of business organizations, several problems have emerged for those organizations in terms of weakness in the issue of improving the reliability of safety management systems to combat and prevent occupational risks, and thus the emergence of the threat to reduce employee satisfaction and stable performance for their business. Thus, given the importance of the foregoing, the study attempted to present a better understanding about the effective role that the requirements of an intelligent safety management system could play in achieving production excellence in cement factories in the Kurdistan Region of Iraq. To achieve this goal, the researcher proceeded to prepare a theoretical framework by making use of the literature of the topic, in addition to adopting the study’s descriptive and analytical approach and using the questionnaire to poll the opinions of the research sample consisting of (201) employees, using the Smart PLS and Spss statistical package for analysis. Therefore, the results of the study showed, based on the opinions and answers of the surveyed sample, that there is a significant correlation and a positive impact between the requirements of the intelligent safety management system and production excellence in general. Accordingly, the study recommended the need for laboratory management to pay attention and increase its eagerness to implement the requirements of the safety management system properly and effectively to provide a safer work environment, towards enhancing employee morale and satisfaction in a way that ensures the achievement of production excellence in the factory as a whole.